Reducing The Culture of Corruption Through The Zakat Social Solidarity Movement - Nur Rohim Yunus; Asep Syarifuddin Hidayat; Muhammad Ishar Helmi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2023)
This article examines the role of zakat social solidarity in reducing the Indonesian culture of corruption. Corruption is pervasive and detrimental to development and the welfare of the people in Indonesia's numerous sectors. In Islam, social solidarity is a fundamental value that encourages Muslims to share their prosperity with those in need through the tithe. This article explains that the practice of tithing social solidarity can play a significant role in preventing and reducing corruption culture. Through qualitative research methods with a literature approach, this article explores an understanding of social solidarity and its impact on reducing the culture of corruption. Various related literature and research are used as references to support the arguments presented. The results of the study state that by practicing zakat, people are empowered economically, educationally and healthfully, thereby reducing social inequality and increasing welfare. In addition to fostering strong social awareness and concern, the practice of zakat reduces harmful behaviors such as corruption and extortion. Social solidarity through zakat also promotes the adoption of ethical and moral values in business, increases public participation in monitoring corruption, and fosters cooperation among economic actors to promote transparency and accountability.